Jātīẏa granthapañjī, Bāṃlā bibhāga, 1958 - Ghosha, Sunīlabihārī (State Bureau of Education, Śikshābibhāga, Paścimabaṅga Sarakāra, 1960)
Bengali publications listed in the Indian National Bibliography, 1958.